Structural characteristics, optical, electrical and electrochemical sensing properties of graphene and multi walled carbon nanotube admixtured bismuth iron oxide composite ceramics. Issue 19 (1st October 2021) - Anandaraj, C.; Venkatapathy, R.; Bharath Sabarish, V.C.; Kalaivani, P.; Durairajan, A.; Graça, M.P.; Valente, M.A.; Gajendiran, J.; Gokul Raj, S.; Ramesh Kumar, G.
Abstract: Graphene and Multi Walled Carbon Nanotubes (MWCNT) admixtured Bismuth Iron Oxide (hereafter referred to BIO) nanocomposite ceramics have been synthesized using the sol-gel process. A comparative study on their structural, optical, dielectrical and electrochemical sensing properties has also been made for the first time in an "as-prepared" state. The X-ray diffraction (XRD) peaks clearly indicate the existence of mixed crystalline phases of BIO with graphene and MWCNT. SEM images reveal the distinct morphologies of BIO nano structures, even in the admixtured phase with graphene and MWCNT. The characteristic vibrations and possible scattering modes of BIO admixtured carbonaceous materials (graphene & MWCNT) have been identified through FT-IR and Raman spectra. Band gap (Eg ) variation was noticed in the synthesized composites upon loading graphene and MWCNT on the BIO matrix. Enhancement of relative permitivity (εr ) has been witnessed in the graphene admixtured BIO composite. This increase is significant, when compared to the MWCNT-BIO composite and it may be due to the effective dispersion of graphene over BIO. The pseudo capacitive behaviour of the BIO composite powder with graphene and MWCNT was also ascertained from the Cyclic Voltammetry (CV) studies.